Utilization and outcomes of massive transfusion protocols in women with and without invasive placentation. (1st November 2020) - Shainker, Scott; Shamshirsaz, Alireza; Haviland, Miriam; O'Brien, Kerry; Redhunt, Allyson; Bateni, Zhoobin; Moaddab, Amirhossein; Fox, Karin; Hui, Shiu-Ki; Belfort, Michael; Dildy, Gary; Hacker, Michele
Abstract: Objective: Our objective was to compare women with and without invasive placentation for whom the massive transfusion protocol (MTP) was activated. In addition, we evaluated the differences in clinical management and blood product utilization between the two groups and described the activation of MTP over time. Study design: This is a retrospective cohort study of women for whom the MTP was activated from January 2012 through July 2016. Two groups were compared, those with invasive placentation (accreta, increta, percreta) and those without. Results: We identified 87 women for whom the MTP was activated, the majority (62.1%) did not have invasive placentation. Women with invasive placentation were more likely to have had a prior cesarean delivery and placenta previa (both p < .001). Women with invasive placentation were more likely to undergo hysterectomy, experience more blood loss, and receive cell salvage (all p ≤ .04). Blood product utilization was similar between the two groups, with the exception of cell-salvage, which was more commonly used for women with invasive placentation. The proportion of deliveries necessitating MTP activation ranged from 1.4 to 2.6 per 1000 deliveries. Conclusion: Invasive placentation accounts for less than half of the cases complicated by activation of an MTP. Cases with invasive placentation were more likely to result in a vertical uterine and skin incision or a hysterectomy. With the exception of cell-salvage, blood product utilization was similar.